Improving Speaking Ability through Memorization Method and Language Learning: An Action Research - Anis Setiyanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Many students in higher education face persistent challenges in English speaking proficiency, often due to limited vocabulary, grammar knowledge, and fluency. This study aimed to improve students’ English speaking skills through the application of the memorization method supported by mobile-assisted language learning. This action research employed the Kemmis and McTaggart model, which includes four cyclical stages: planning, action, observation, and reflection. The research involved fourth-semester students in the Islamic Education Study Program at Muhammadiyah University Jakarta. A mixed-methods approach was used, incorporating both qualitative data (from observations and interviews) and quantitative data (from pre-cycle and three subsequent cycle tests). Data were analyzed using descriptive statistics and thematic interpretation. The results showed progressive improvement in students’ speaking performance across all cycles. In the pre-cycle phase, students’ average scores fell into the unsatisfactory category. These increased to moderately satisfactory in Cycle 1 and Cycle 2, and reached the satisfactory category in Cycle 3, with an average score of 81%. Students demonstrated notable gains in pronunciation, vocabulary, grammar usage, and fluency. Additionally, the integration of mobile devices for memorization practice enhanced engagement and accessibility in learning. The findings suggest that the memorization method, when combined with mobile learning tools, can significantly enhance students' English speaking ability. This approach offers a practical pedagogical strategy to address common barriers in speaking skills among EFL learners.